PENERAPAN METODE UCD UNTUK PERANCANGAN UI DAN UX DALAM MEMBANGUN FITUR MENTOR ON DEMAND DAN LIVE CHAT PADA WEBSITE SKILVUL - Youky Arie Sandi; Imam Maruf Nugroho; Yudhi Raymond Ramadhan (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
The user interface (UI) plays an important role in giving the user a good initial impression of the visuals of an application or website. Meanwhile, User Experience (UX) helps build interaction between users and the application system or website. UI and UX design is very influential for user comfort, so it needs an accurate analysis according to user needs. Skilvul is a technology education platform that currently wants Mentor on Demand and Live Chat features that aim to help users conduct consultations and learning discussions with mentors. By creating these features, UI and UX design will be carried out first using the User Centered Design (UCD) method. The results of the design in this study were carried out using the Single Ease Questionnaire (SEQ) testing method. Through the SEQ questionnaire, the average value is 6.5. Based on these results, it proves that the results of UI and UX design in building Mentor on Demand and Live Chat features can be categorized as easy and according to user needs.